2011
DOI: 10.1101/gr.108563.110
|View full text |Cite
|
Sign up to set email alerts
|

Clcn4-2 genomic structure differs between the X locus in Mus spretus and the autosomal locus in Mus musculus: AT motif enrichment on the X

Abstract: In Mus spretus, the chloride channel 4 gene Clcn4-2 is X-linked and dosage compensated by X up-regulation and X inactivation, while in the closely related mouse species Mus musculus, Clcn4-2 has been translocated to chromosome 7. We sequenced Clcn4-2 in M. spretus and identified the breakpoints of the evolutionary translocation in the Mus lineage. Genetic and epigenetic differences were observed between the 59ends of the autosomal and X-linked loci. Remarkably, Clcn4-2 introns have been truncated on chromosome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 55 publications
1
17
0
Order By: Relevance
“…Wang et al (2006) reported that the majority of 3-mers and 5-mers enriched around human genes subject to X inactivation, but not around escape genes, are AT-rich (Wang et al 2006). This is consistent with our recent observations that mouse escape genes contain fewer AT-rich motifs than genes subject to X inactivation (Nguyen et al 2011). The role of AT-rich motifs in the process of silencing by X inactivation is supported by findings that SATB1, a protein that specifically binds AT-rich DNA, both binds to the Xi and causes disruption in the silencing function of Xist if mutated in mouse cells (Agrelo et al 2009).…”
Section: Molecular Mechanisms Of Escapesupporting
confidence: 93%
See 1 more Smart Citation
“…Wang et al (2006) reported that the majority of 3-mers and 5-mers enriched around human genes subject to X inactivation, but not around escape genes, are AT-rich (Wang et al 2006). This is consistent with our recent observations that mouse escape genes contain fewer AT-rich motifs than genes subject to X inactivation (Nguyen et al 2011). The role of AT-rich motifs in the process of silencing by X inactivation is supported by findings that SATB1, a protein that specifically binds AT-rich DNA, both binds to the Xi and causes disruption in the silencing function of Xist if mutated in mouse cells (Agrelo et al 2009).…”
Section: Molecular Mechanisms Of Escapesupporting
confidence: 93%
“…Xist cis-spreading along the X is still not well understood, but specific motifs may be involved. Notably, repeat elements such as interspersed repetitive elements (LINE-1) are critical for the formation of a silenced compartment and AT-rich motifs may also be involved (Agrelo et al 2009; Chow et al 2010; Nguyen et al 2011). Xist recruits the polycomb complex PRC2, which mediates the initial histone changes (e.g., methylation of lysine 27 of histone H3) on the inactive X (Plath et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…At the autosomal locus, the size of Clcn4-2 is dramatically reduced by deletions of large portions of its introns. AT-rich sequence motifs deleted on the autosome but preserved on the X are abundant throughout the entire X (118). Whether these motifs are implicated in either X upregulation and/or X inactivation remains to be investigated.…”
Section: Targeting and Organizing The X: Motifs And Nuclear Positionmentioning
confidence: 99%
“…While fishes encode only two WWC genes, most other vertebrates including frog, rat and human have all three WWC members (3). Notably, due to a chromosomal translocation event in the evolution of the mouse lineage, Mus musculus expresses only KIBRA/WWC1 and WWC2 but lacks WWC3 (4). Whether there is functional interplay among the WWC proteins is almost completely unknown.…”
Section: Kibra Gene and Wwc Familymentioning
confidence: 99%